Research response to coronavirus disease 2019 needed better coordination and collaboration: a living mapping of registered trials - Nguyen, Van Thu; Rivière, Philippe; Ripoll, Pierre; Barnier, Julien; Vuillemot, Romain; Ferrand, Gabriel; Cohen-Boulakia, Sarah; Ravaud, Philippe; Boutron, Isabelle; Alawadhi, Solaf; Amer-Yahia, Sihem; Ávila, Camila; et al. (Elsevier Inc., 2020)
Objectives: Researchers worldwide are actively engaging in research activities to search for preventive and therapeutic interventions against coronavirus disease 2019 (COVID-19). Our aim was to describe the planning of randomized controlled trials (RCTs) in terms of timing related to the course of the COVID-19 epidemic and research question evaluated. Study Design and Setting: We performed a living mapping of RCTs registered in the WHO International Clinical Trials Registry Platform. We systematically search the platform every week for all RCTs evaluating preventive interventions and treatments for COVID-19 and created a publicly available interactive mapping tool at https://covid-nma.com to visualize all trials registered. Results: By August 12, 2020, 1,568 trials for COVID-19 were registered worldwide. Overall, the median ([Q1–Q3]; range) delay between the first case recorded in each country and the first RCT registered was 47 days ([33–67]; 15–163). For the 9 countries with the highest number of trials registered, most trials were registered after the peak of the epidemic (from 100% trials in Italy to 38% in the United States). Most trials evaluated treatments (1,333 trials; 85%); only 223 (14%) evaluated preventive strategies and 12 postacute period intervention. A total of 254 trials were planned to assess different regimens of hydroxychloroquine with an expected sample size of 110,883 patients. Conclusion: This living mapping analysis showed that COVID-19 trials have relatively small sample size with certain redundancy in research questions. Most trials were registered when the first peak of the pandemic has passed.